Negative electrode active material for non-aqueous electrolyte secondary battery and method for producing same
By using carbon-coated negative electrode active material particles with specific lithium content and silicon compound composition, the challenges of instability and limited performance in silicon-based battery materials are addressed, resulting in improved stability and cycle life.
Patent Information
- Application Number
- JP2022006556
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-19
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2042-01-19
AI Technical Summary
Existing negative electrode active materials for nonaqueous electrolyte secondary batteries, particularly those using silicon compounds, face challenges such as instability in water-based slurries, limited improvement in battery characteristics, and issues with electrolyte decomposition leading to reduced cycle characteristics.
The development of negative electrode active material particles coated with carbon, containing specific lithium content (9.7% to 13.2% by mass) and comprising silicon compounds (SiO)x with 0.5≦x≦1.6, where at least a portion is Li2SiO3, and having a controlled crystallite size and lithium distribution, enhances stability and performance.
This approach improves the stability of water-based slurries, enhances battery capacity, maintains initial efficiency, and extends cycle life by reducing irreversible capacity and electrolyte decomposition.
Smart Images

Figure 0007659512000010 
Figure 0007659512000011 
Figure 0007659512000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode active material for a non-aqueous electrolyte secondary battery and a method for producing the same. [Background technology]
[0002] In recent years, small electronic devices such as mobile terminals have become widespread, and there is a strong demand for further miniaturization, weight reduction, and longer life. In response to such market demands, development of secondary batteries that are small, lightweight, and capable of obtaining high energy density has been promoted. The application of these secondary batteries is being considered not only for small electronic devices, but also for large electronic devices such as automobiles and power storage systems such as homes.
[0003] Among these, lithium-ion secondary batteries are attracting great attention because they can be easily made small and have a high capacity, and because they offer a higher energy density than lead-acid batteries and nickel-cadmium batteries.
[0004] The lithium ion secondary battery includes a positive electrode, a negative electrode, a separator, and an electrolyte solution, and the negative electrode contains a negative electrode active material involved in charge and discharge reactions.
[0005] While carbon materials (carbon-based active materials) are widely used as the negative electrode active material, recent market demands have called for further improvements in battery capacity. To improve battery capacity, the use of silicon as the negative electrode active material is being considered. This is because the theoretical capacity of silicon (4199mAh / g) is more than 10 times greater than the theoretical capacity of graphite (372mAh / g), and a significant improvement in battery capacity can be expected. In the development of silicon materials as negative electrode active materials, not only silicon itself but also alloys and compounds such as oxides are being considered. In addition, the active material shape is being considered, ranging from the standard coating type for carbon-based active materials to an integrated type that is directly deposited on the current collector.
[0006] However, when silicon is used as the main raw material for the negative electrode active material, the negative electrode active material expands and contracts during charging and discharging, making it prone to cracking, mainly near the surface layer of the negative electrode active material. In addition, ionic substances are generated inside the active material, making the negative electrode active material prone to cracking. When the surface layer of the negative electrode active material cracks, a new surface is formed, and the reaction area of the active material increases. At this time, a decomposition reaction of the electrolyte occurs on the new surface, and a coating, which is a decomposition product of the electrolyte, is formed on the new surface, consuming the electrolyte. This makes the cycle characteristics prone to deterioration.
[0007] Up to now, in order to improve the initial efficiency and cycle characteristics of a battery, attempts have been made to dope lithium into silicon oxide, which is an anode active material (see, for example, Patent Document 1 below). By incorporating lithium into silicon oxide, which is an anode active material, when this is used as an anode, it is possible to reduce irreversible components, and therefore improvement in initial efficiency can be expected. In addition, this improvement in initial efficiency is expected to increase the capacity of lithium-ion secondary batteries.
[0008] However, although the initial efficiency of the negative electrode active material silicon oxide is improving, the current LiCoO 2 The efficiency is still lower than that of positive electrode materials such as lithium cobalt oxide (for example, see Patent Document 2), and further efficiency improvement is required.
[0009] In addition, the lithium compound in the silicon compound dissolves in water and becomes alkaline, which reacts with the silicon compound to generate hydrogen gas, which causes coating defects when preparing an aqueous slurry using such a negative electrode active material, leading to a deterioration in battery characteristics.
[0010] For this reason, methods for maintaining stability in aqueous slurries have been developed. For example, a method of doping silicon compound particles with lithium and then performing a surface treatment (e.g., Patent Document 3) and a method of converting the silicon compound particles into lithium silicate that is stable in water (e.g., Patent Document 4) have been proposed. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2011-222153 A [Patent Document 2] JP 2020-113495 A [Patent Document 3] International Publication No. WO2017 / 051500 [Patent Document 4] JP 2015-153520 A Summary of the Invention [Problem to be solved by the invention]
[0012] However, when referring to the examples of the lithium silicate formation method disclosed in Patent Document 4, washing with an acidic aqueous solution is performed after lithium doping in order to obtain the target lithium silicate, and the doped lithium is extracted to an amount stable in water by the acid washing. Therefore, the amount of lithium that can be doped is limited, and as a result, there is a problem that the improvement of the battery characteristics is also limited.
[0013] The present invention has been made in view of the above-mentioned problems, and aims to provide a negative electrode active material for non-aqueous electrolyte secondary batteries that exhibits high stability even in an aqueous slurry and has excellent battery characteristics (initial efficiency and capacity retention rate). Another aim of the present invention is to provide a method for producing such negative electrode active material particles. [Means for solving the problem]
[0014] In order to achieve the above object, the present invention provides a negative electrode active material particle, the negative electrode active material particle being made of a silicon compound (SiO x0.5≦x≦1.6) particles, wherein the negative electrode active material particles are at least partially coated with a carbon material, the negative electrode active material particles contain Li, the Li content is 9.7% by mass or more and less than 13.2% by mass with respect to the negative electrode active material particles, and at least a portion of the Li is Li 2 SiO 3 When the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα radiation, the intensity of the peak at 2θ=47.5° due to Si obtained by the X-ray diffraction is Ia, and the intensity of Li obtained by the X-ray diffraction is Ib. 2 SiO 3 The negative electrode active material for a non-aqueous electrolyte secondary battery is characterized in that the peak intensity Ib of the peak at about 2θ=18.7° resulting from satisfies 1≦Ib / Ia≦18.
[0015] The negative electrode active material of the present invention has a high battery capacity because it contains negative electrode active material particles containing silicon compound particles. In addition, the SiO 2 in the silicon compound, which becomes unstable when lithium is inserted and extracted during charging and discharging of the battery, is not easily destabilized. 2 Since the component part is modified to another Li compound in advance, it is possible to reduce the irreversible capacity generated during charging. In addition, since the negative electrode active material particles contain a carbon coating, they have appropriate electrical conductivity, and the capacity retention rate and initial efficiency can be improved. Furthermore, since the Li content of the negative electrode active material particles is 9.7 mass% or more and less than 13.2 mass%, LiCoO 2 It is possible to obtain an initial efficiency equivalent to that of positive electrode materials such as silicon oxide, and stability against water can also be ensured. If the Li content is less than 9.7 mass%, the initial efficiency of the negative electrode active material containing silicon oxide is significantly lower than the initial efficiency of the positive electrode material. If the Li content exceeds 13.2 mass%, stability against water decreases. In addition, the negative electrode active material particles contain Li, which is a lithium compound that is stable against water. 2 SiO 3By containing Li, gas does not generate even in the aqueous slurry, and a stable state can be maintained, resulting in improved initial efficiency and capacity retention. In addition, the negative electrode active material particles have an intensity Ia at 2θ=47.5° due to the Si peak obtained by X-ray diffraction, and Li 2 SiO 3 The above-mentioned effect can be achieved by satisfying 1≦Ib / Ia≦18 for the intensity Ib at around 2θ=18.7° due to the above. When the intensity ratio Ib / Ia is greater than 18, gas is generated in the aqueous slurry, and the stability of the slurry cannot be ensured. When the intensity ratio Ib / Ia is less than 1, the doped Li is not stabilized, and gas is generated in the aqueous slurry. Hereinafter, the negative electrode active material particles containing silicon compound particles are also referred to as silicon-based active material particles. The negative electrode active material containing the silicon-based active material particles is also referred to as silicon-based active material.
[0016] At this time, the negative electrode active material particles have a crystalline Li 2 CO 3 and LiOH H 2 It is preferable that it does not contain O.
[0017] In addition, the negative electrode active material particles have a crystalline Li 2 CO 3 and LiOH H 2 and when the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα radiation, the X-ray diffraction measurement results in a Li 2 CO 3 The peak intensity Ic at 2θ=21° due to the above satisfies 0≦Ic / Ia≦10, and the LiOH H obtained by the X-ray diffraction 2 The peak intensity Id attributable to O near 2θ=32° may satisfy 0≦Id / Ia≦20.
[0018] The outermost layer of the negative electrode active material particles is crystalline Li 2 CO 3 and LiOH H 2When at least one ionic substance such as Li, O, is contained, the binding property of the binder is improved when the aqueous slurry is prepared. In addition, when the above Ic / Ia and Id / Ia are Ic / Ia≦10 and Id / Ia≦20, the pH of the aqueous slurry is not raised too much when the aqueous slurry is prepared, so that gas generation and a decrease in the viscosity of the slurry can be prevented. In addition, from the viewpoints of both improving the binding property of the binder and increasing the pH, the crystalline Li 2 CO 3 , LiOH H 2 It is preferable that O is not included. In this case, it is preferable that 0=Ic / Ia, 0=Id / Ia.
[0019] In addition, in the negative electrode active material particles of the present invention, when the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα radiation, it is preferable that the crystallite size resulting from the Si(220) crystal plane obtained by the X-ray diffraction is 5 nm or less.
[0020] Thus, if the crystallite size resulting from the Si(220) crystal plane is within the above range, better battery characteristics can be obtained.
[0021] In addition, when the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα rays, the Li 2 SiO 3 It is preferable that the half-width of the peak at about 2θ=18.7° due to is 0.5° or more and 3.0° or less.
[0022] Thus, the Li 2 SiO 3 When the half width of the peak at about 2θ=18.7° caused by is 0.5° or more and 3.0° or less, the elution of alkaline components into the aqueous slurry can be suppressed, and better battery characteristics can be obtained.
[0023] In addition, the negative electrode active material particles 29It is preferable that the compound has at least one peak in at least one of the following chemical shift values obtained from a Si-MAS-NMR spectrum: a region of −80 ppm or more and less than −70 ppm, a region of −70 ppm or more and less than −60 ppm, and a region of −60 ppm or more and less than −30 ppm.
[0024] In the negative electrode active material particles containing silicon compound particles, the peak in the chemical shift value range of -60 ppm to less than -30 ppm is due to low-valence silicon oxide, and the peak in the range of -70 ppm to less than -60 ppm is due to Li 6 S 2 O 7 The peaks around -80ppm to -70ppm are due to Li 2 SiO 3 Therefore, by having at least one peak in at least one of the above regions, it is possible to suppress the elution of alkaline components into the aqueous slurry, and better battery characteristics can be obtained. 6 S 2 O 7 Although there may be a peak derived from the component, it is more preferable that there is substantially no peak. That is, it is more preferable that there is at least one of a peak in the vicinity of from -60 ppm to less than -30 ppm and a peak in the vicinity of from -80 ppm to less than -70 ppm, rather than a peak in the vicinity of from -70 ppm to less than -60 ppm.
[0025] In addition, the negative electrode active material particles 29 When the peak intensity of a peak obtained in the chemical shift value range of -60 ppm or more and less than -30 ppm from the Si-MAS-NMR spectrum is defined as Ie, the peak intensity of a peak obtained in the chemical shift value range of -70 ppm or more and less than -60 ppm is defined as If, and the peak intensity of a peak obtained in the chemical shift value range of -80 ppm or more and less than -70 ppm is defined as Ig, it is preferable that 0≦Ie / Ig≦0.23 and 0≦If / Ig≦1.1.
[0026] Silicon-based compound particles having such NMR peaks can suppress the elution of alkaline components into the aqueous slurry, and thus obtain better battery characteristics. As described above, the peaks in the vicinity of the region of -70 ppm or more and less than -60 ppm are Li 6 S 2 O 7 It is substantially preferable that this peak does not exist, and it is more preferable that If / Ig=0.
[0027] The amount of carbon coating on the negative electrode active material particles is preferably 0.3% by mass to 10% by mass based on the total amount of the silicon compound and the carbon coating layer.
[0028] In this way, if the amount of carbon coating on the negative electrode active material particles is 0.3 mass % or more and 10 mass % or less, sufficient conductivity can be ensured, and better battery characteristics can be obtained.
[0029] The intensity ratio ID / IG of the D band to the G band as determined by Raman spectroscopy of the negative electrode active material particles is preferably 0.4≦ID / IG≦1.1.
[0030] In this way, if 0.4≦ID / IG≦1.1, peeling of the carbon film due to expansion and contraction and side reactions on the carbon surface can be suppressed, resulting in better battery characteristics.
[0031] In addition, it is preferable that the intensity ratio I G' / I G of the G band to the G band in Raman spectroscopy of the negative electrode active material particles satisfies 0≦I G' / I G ≦0.05.
[0032] In this way, if 0≦IG′ / IG≦0.05, Li is inserted uniformly from the entire surface of the carbon during charging, and better battery characteristics are obtained.
[0033] In addition, the ratio ISi / IG of the Si peak intensity to the G band intensity in Raman spectroscopy of the negative electrode active material particles is preferably 0≦ISi / IG≦1.0.
[0034] Thus, when 0≦ISi / IG≦1.0, surface exposure of the silicon-based compound particles can be suppressed and gas generation in the aqueous slurry can be delayed, resulting in better battery characteristics.
[0035] The silicon compound particles preferably have a median diameter of 0.5 μm or more and 20 μm or less.
[0036] If the median diameter is 0.5 μm or more, the area on the surface of the negative electrode active material particles where side reactions occur is small, so that Li is not consumed excessively and the cycle retention rate of the battery can be maintained high. Also, if the median diameter is 20 μm or less, the expansion upon insertion of Li is small, so that the battery is less likely to break and cracks are less likely to occur. Furthermore, since the expansion of the negative electrode active material particles is small, for example, a negative electrode active material layer made by mixing a carbon active material with a commonly used silicon-based active material is less likely to be destroyed.
[0037] In order to achieve the above object, the present invention also provides a non-aqueous electrolyte secondary battery comprising any one of the above negative electrode active materials for non-aqueous electrolyte secondary batteries.
[0038] Such a secondary battery has a high cycle retention rate and initial efficiency, and can be advantageously produced industrially.
[0039] In order to achieve the above object, the present invention provides a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery, comprising the steps of: x (x≦0.5≦x≦1.6), coating at least a portion of the silicon compound particles with a carbon material, and incorporating Li into the silicon compound particles to form Li 2 SiO 3and adjusting the Li content to 9.7% by mass or more and less than 13.2% by mass with respect to the negative electrode active material particles, and when the negative electrode active material particles produced are measured by X-ray diffraction using Cu-Kα rays, the intensity Ia of the peak attributable to Si obtained by the X-ray diffraction and the intensity Ib of the Li obtained by the X-ray diffraction are 2 SiO 3 The present invention provides a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery, further comprising a step of selecting a material having a peak intensity Ib of a peak at about 2θ=18.7° resulting from the above satisfying 1≦Ib / Ia≦18.
[0040] Such a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery can provide a non-aqueous negative electrode active material that takes advantage of the inherent properties of silicon oxide modified with Li and has a high battery capacity and a good cycle retention rate. Effect of the Invention
[0041] The negative electrode active material of the present invention can improve the stability of the slurry prepared during the manufacture of the secondary battery, and the use of this slurry can form an industrially usable coating film, which can substantially improve the battery capacity, cycle characteristics, and initial charge / discharge characteristics. In addition, the secondary battery of the present invention containing this negative electrode active material can be produced industrially with advantage, and has good battery capacity, cycle characteristics, and initial charge / discharge characteristics. In addition, the same effect can be obtained in electronic devices, power tools, electric vehicles, power storage systems, etc. using the secondary battery of the present invention.
[0042] In addition, the method for producing a negative electrode active material of the present invention can produce a negative electrode material that can improve the stability of the slurry prepared during the production of a secondary battery, and can also improve the battery capacity, cycle characteristics, and initial charge / discharge characteristics. [Brief description of the drawings]
[0043] [Figure 1] 1 is a cross-sectional view showing an example of the configuration of a negative electrode for a non-aqueous electrolyte secondary battery containing the negative electrode active material of the present invention. [Diagram 2] 1 is an in-bulk reforming apparatus that can be used when producing the negative electrode active material of the present invention. [Diagram 3] FIG. 1 is an exploded view showing a configuration example (laminate film type) of a lithium ion secondary battery including the negative electrode active material of the present invention. [Figure 4] 2 is an example of an XRD chart of the negative electrode active material of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0044] Hereinafter, the present invention will be described in detail with reference to the preferred embodiments, but the present invention is not limited thereto.
[0045] As mentioned above, as one method for increasing the battery capacity of lithium-ion secondary batteries, the use of a negative electrode mainly made of silicon-based active material as the negative electrode of lithium-ion secondary batteries has been considered. Lithium-ion secondary batteries using silicon-based active materials as the main material are expected to have initial efficiency and cycle characteristics similar to those of lithium-ion secondary batteries using carbon materials (carbon-based negative electrode active materials), but no negative electrode material has been proposed that shows cycle stability equivalent to that of nonaqueous electrolyte secondary batteries using carbon materials. In particular, silicon compounds containing oxygen have a lower initial efficiency than carbon materials, so the improvement in battery capacity has been limited.
[0046] Therefore, the present inventors conducted extensive research in order to obtain a negative electrode active material that enables easy production of a nonaqueous electrolyte secondary battery that has a high battery capacity as well as good cycle characteristics and initial efficiency, and have arrived at the present invention.
[0047] [Negative electrode active material of the present invention] The negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention has negative electrode active material particles. The negative electrode active material particles are made of a silicon compound (SiO x(x≦0.5≦x≦1.6) particles. Furthermore, at least a portion of the negative electrode active material particles (silicon-based active material particles) is coated with a carbon material. Furthermore, the negative electrode active material particles (silicon-based active material particles) contain Li, and the content of the Li is 9.7% by mass or more and less than 13.2% by mass with respect to the negative electrode active material particles. At least a portion of the Li is Li 2 SiO 3 Furthermore, when the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα radiation, the intensity of the peak at 2θ=47.5° due to Si obtained by the X-ray diffraction is Ia, and the intensity of the peak at 2θ=47.5° due to Li obtained by the X-ray diffraction is Ib. 2 SiO 3 The peak intensity Ib of the peak at about 2θ=18.7° due to satisfies 1≦Ib / Ia≦18.
[0048] Such a negative electrode active material has a high battery capacity because it contains negative electrode active material particles containing a silicon compound. In addition, the SiO in the silicon compound becomes unstable when lithium is inserted and removed during charging and discharging of the battery. 2 Since the component part is modified to another Li compound in advance, it is possible to reduce the irreversible capacity that occurs during charging. In addition, since the negative electrode active material particles contain a carbon coating, they have appropriate conductivity, which can improve the capacity retention rate and initial efficiency. Furthermore, the negative electrode active material particles contain Li, which is a lithium compound that is stable against water. 2 SiO 3 (a type of silicate), gas is not generated even in an aqueous slurry, and a stable state can be maintained, resulting in improved initial efficiency and capacity retention. In X-ray diffraction using Cu-Kα radiation, the negative electrode active material particles have an intensity Ia at 2θ=47.5° due to the Si peak, and a Li 2 SiO 3 The above-mentioned effects can be achieved by satisfying the relationship 1≦Ib / Ia≦18 for the intensity ratio Ib / Ia at around 2θ=18.7° due to the above. If the intensity ratio Ib / Ia is greater than 18, gas will be generated in the aqueous slurry, and the stability of the slurry cannot be ensured.
[0049] An example of the XRD spectrum of the negative electrode active material of the present invention is shown in Figure 4. This is the XRD spectrum of the negative electrode active material of Example 2-1 described later.
[0050] The peak intensity can be calculated by XRD peak analysis, for example, under the following conditions. XRD measurement Equipment: Bruker D2 PHASER ·X-ray source:Cu Divergence slit: 0.5° ·Inlet side solar: 4° - Receiving side solar: 4° Calculation of peak intensity Software: DIFFRAC.EVA
[0051] [Negative electrode composition] Next, the configuration of the negative electrode of the secondary battery containing such a negative electrode active material of the present invention will be described.
[0052] Fig. 1 shows a cross-sectional view of a negative electrode including the negative electrode active material of the present invention. As shown in Fig. 1, a negative electrode 10 has a negative electrode active material layer 12 on a negative electrode current collector 11. This negative electrode active material layer 12 may be provided on both sides or only one side of the negative electrode current collector 11. Furthermore, if the negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention is used, the negative electrode current collector 11 may not be necessary.
[0053] [Negative electrode current collector] The negative electrode current collector 11 is made of a material having excellent electrical conductivity and excellent mechanical strength. Examples of the conductive material that can be used for the negative electrode current collector 11 include copper (Cu) and nickel (Ni). It is preferable that this conductive material does not form an intermetallic compound with lithium (Li).
[0054] The negative electrode current collector 11 preferably contains carbon (C) and / or sulfur (S) in addition to the main elements. This is because the physical strength of the negative electrode current collector is improved. In particular, when the current collector has an active material layer that expands during charging, if the current collector contains the above elements, this has the effect of suppressing deformation of the electrode including the current collector. The content of the above contained elements is not particularly limited, but is preferably 100 ppm or less. This is because a higher deformation suppression effect can be obtained.
[0055] The surface of the negative electrode current collector 11 may be roughened or may not be roughened. The roughened negative electrode current collector is, for example, a metal foil that has been electrolytically treated, embossed, or chemically etched. The unroughened negative electrode current collector is, for example, a rolled metal foil.
[0056] [Negative electrode active material layer] The negative electrode active material layer 12 may contain a plurality of types of negative electrode active materials, such as a carbon-based active material, in addition to silicon-based active material particles. Furthermore, in terms of battery design, it may contain other materials, such as a thickener (also called a "binding agent" or "binder") and a conductive assistant. The negative electrode active material may be in the form of particles.
[0057] As described above, the negative electrode active material of the present invention is SiO x (0.5≦x≦1.6). The silicon-based active material particles are made of silicon oxide material (SiO x (0.5≦x≦1.6), and it is preferable that x is close to 1 in the composition. This is because high cycle characteristics can be obtained. Note that the composition of the silicon oxide material in the present invention does not necessarily mean 100% purity, and may contain trace amounts of impurity elements and Li.
[0058] In addition, in the present invention, the lower the crystallinity of the silicon compound (crystallinity of Si crystallites), the better. Specifically, when the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα rays, it is preferable that the crystallite size due to the Si (220) crystal plane obtained by the X-ray diffraction is 5 nm or less. It is also preferable that the half-width of the diffraction peak due to the (220) crystal plane obtained by X-ray diffraction is 1.5° or more. In particular, it is preferable that the diffraction peak is broad and has no clear peak. In this way, the particularly low crystallinity and the small amount of Si crystals not only improves the battery characteristics, but also allows the generation of a stable Li compound.
[0059] The crystallite size due to the Si(220) crystal plane cannot be calculated by normal analysis, but can be calculated by XRD peak analysis. Calculation of crystallite size by XRD can be performed, for example, under the following conditions. For broad peaks, analysis software TOPAS can be used, for example, under the following conditions. XRD measurement Equipment: Bruker D2 PHASER ·X-ray source:Cu Divergence slit: 0.5° ·Inlet side solar: 4° - Receiving side solar: 4° Calculation of crystallite size Analysis software: DIFFRAC.TOPAS Analysis method: Peak fitting method Emission Profile: CuKa5.lam Function: FP (First Principle) function Refinement Option: Select “Calculate Error” and “Use Extrapolation”
[0060] The median diameter of the silicon compound particles is not particularly limited, but is preferably 0.5 μm or more and 20 μm or less (volume basis). This is because in this range, lithium ions are easily absorbed and released during charging and discharging, and the silicon-based active material particles are less likely to crack. If the median diameter is 0.5 μm or more, the surface area is not too large, so side reactions are less likely to occur during charging and discharging, and the irreversible capacity of the battery can be reduced. On the other hand, if the median diameter is 20 μm or less, the silicon-based active material particles are less likely to crack and new surfaces are less likely to appear, which is preferable.
[0061] Furthermore, in the present invention, the silicon-based active material contains Li as the Li compound contained in the silicon compound. 2 SiO 3 In addition to Li 4 SiO 4 Or Li 6 S 2 O 7 Li may be present. 2 SiO 3 In addition to Li 4 SiO 4 , Li 6 S 2 O 7 Li silicates such as these are relatively more stable than other Li compounds, so silicon-based active materials containing these Li compounds can provide more stable battery characteristics. These Li compounds are formed inside the silicon compounds by the SiO 2 It can be obtained by selectively changing part of the components to Li compounds and modifying silicon compounds.
[0062] The amount of Li compounds in the negative electrode active material particles and the silicon compound particles can be quantified by NMR (nuclear magnetic resonance) and XPS (X-ray photoelectron spectroscopy). The XPS and NMR measurements can be performed, for example, under the following conditions. XPS ·Equipment: X-ray photoelectron spectrometer, X-ray source: monochromatic Al Kα radiation, X-ray spot diameter: 100μm, Ar ion gun sputtering conditions: 0.5kV 2mm×2mm. 29 Si MAS NMR (Magic Angle Spinning Nuclear Magnetic Resonance) Equipment: Bruker 700 NMR spectrometer; Probe: 4mm HR-MAS rotor 50μL, Sample rotation speed: 10kHz, ·Measurement environment temperature: 25℃
[0063] In addition, in the present invention, when modifying the silicon compound, electrochemical methods, modification by oxidation-reduction reaction, and physical methods such as thermal doping can be used. In particular, when the silicon compound is modified using electrochemical methods and modification by oxidation-reduction, the battery characteristics of the negative electrode active material are improved. In addition, in the modification, it is preferable to not only insert Li into the silicon compound, but also stabilize the Li compound by heat treatment and desorb Li from the silicon compound. This further improves the stability against the slurry, such as the water resistance of the negative electrode active material. However, it is necessary to set the Li content and peak intensity ratio Ib / Ia within the range of the present invention.
[0064] In the negative electrode active material of the present invention, the silicon compound is 29 The chemical shift values obtained from the Si-MAS-NMR spectrum have a peak derived from the low valence region of silicon oxide given in the vicinity of the region of -60 ppm to less than -30 ppm, and a peak derived from Li given in the vicinity of the region of -70 ppm to less than -60 ppm. 6 S 2 O 7 The peak is derived from the Li region, which is given in the region between -80 ppm and -70 ppm. 2 SiO 3 In this way, by modifying the material to Li silicate, the stability against the slurry is improved.
[0065] As described above, in the present invention, the silicon compound particles in the silicon-based active material particles include a carbon coating on at least a portion of the surface, and therefore, an appropriate electrical conductivity can be obtained.
[0066] In the negative electrode active material of the present invention, the negative electrode active material particles have a crystalline Li 2 CO 3 and LiOH H 2 and when the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα radiation, the X-ray diffraction measurement results in a Li 2 CO 3 The peak intensity Ic at 2θ=21° due to the above satisfies 0≦Ic / Ia≦10, and the LiOH H obtained by the X-ray diffraction 2 The peak intensity Id attributable to O near 2θ=32° can be made to satisfy 0≦Id / Ia≦20.
[0067] In this way, the crystalline Li 2 CO 3 and LiOH H 2 When at least one of the ionic substances, Ic / Ia and Id / Ia, is contained, the binding property of the binder is improved when the aqueous slurry is prepared. In addition, when the above Ic / Ia and Id / Ia are Ic / Ia≦10 and Id / Ia≦20, the pH of the aqueous slurry is not increased too much when the aqueous slurry is prepared, which can prevent gas generation and a decrease in the viscosity of the slurry.
[0068] In the negative electrode active material of the present invention, in particular, the negative electrode active material particles have a crystalline Li 2 CO 3 and LiOH H 2 It is preferable that the binder does not contain O. From the viewpoints of both improving the binder binding property and increasing the pH, it is preferable to use substantially crystalline Li 2 CO 3 , LiOH H 2 It is preferable that O is not included. In this case, it is preferable that 0=Ic / Ia, 0=Id / Ia.
[0069] In addition, in the negative electrode active material of the present invention, when the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα rays, the Li 2 SiO3 It is preferable that the half-width of the peak at 2θ=18.7° due to Li obtained by X-ray diffraction is 0.5° or more and 3.0° or less. 2 SiO 3 When the half width of the peak at about 2θ=18.7° caused by is 0.5° or more and 3.0° or less, the elution of alkaline components into the aqueous slurry can be suppressed, and better battery characteristics can be obtained.
[0070] In addition, the negative electrode active material particles 29 It is preferable that the compound has at least one peak in at least one of the following chemical shift values obtained from a Si-MAS-NMR spectrum: a region of −80 ppm or more and less than −70 ppm, a region of −70 ppm or more and less than −60 ppm, and a region of −60 ppm or more and less than −30 ppm.
[0071] In the negative electrode active material particles containing silicon compound particles, the peak in the chemical shift value range of -60 ppm to less than -30 ppm is due to low-valence silicon oxide, and the peak in the range of -70 ppm to less than -60 ppm is due to Li 6 S 2 O 7 The peaks around -80ppm to -70ppm are due to Li 2 SiO 3 Therefore, by having at least one peak in at least one of the above regions, it is possible to suppress the elution of alkaline components into the aqueous slurry, and better battery characteristics can be obtained. 6 S 2 O 7 Although there may be a peak derived from the component, it is more preferable that there is substantially no peak. That is, it is more preferable that there is at least one of a peak in the vicinity of from -60 ppm to less than -30 ppm and a peak in the vicinity of from -80 ppm to less than -70 ppm, rather than a peak in the vicinity of from -70 ppm to less than -60 ppm.
[0072] In addition, the negative electrode active material particles 29 When the peak intensity of a peak obtained in the chemical shift value range of -60 ppm or more and less than -30 ppm from the Si-MAS-NMR spectrum is defined as Ie, the peak intensity of a peak obtained in the chemical shift value range of -70 ppm or more and less than -60 ppm is defined as If, and the peak intensity of a peak obtained in the chemical shift value range of -80 ppm or more and less than -70 ppm is defined as Ig, it is preferable that 0≦Ie / Ig≦0.23 and 0≦If / Ig≦1.1.
[0073] Silicon-based compound particles having such NMR peaks can suppress the elution of alkaline components into the aqueous slurry, and thus obtain better battery characteristics. As described above, the peaks in the vicinity of the region of -70 ppm or more and less than -60 ppm are Li 6 S 2 O 7 It is substantially preferable that this peak does not exist, and it is more preferable that If / Ig=0.
[0074] In the negative electrode active material of the present invention, the amount of carbon coating on the negative electrode active material particles is preferably 0.3% by mass or more and 10% by mass or less based on the total of the silicon compound and the carbon coating layer. In this way, if the amount of carbon coating on the negative electrode active material particles is 0.3% by mass or more and 10% by mass or less, sufficient conductivity can be ensured, and better battery characteristics can be obtained.
[0075] In the negative electrode active material of the present invention, the intensity ratio ID / IG of the D band to the G band as determined by Raman spectroscopy of the negative electrode active material particles is preferably 0.4≦ID / IG≦1.1. If 0.4≦ID / IG≦1.1, peeling of the carbon film due to expansion and contraction and side reactions on the carbon surface can be suppressed, resulting in better battery characteristics.
[0076] In the negative electrode active material of the present invention, the intensity ratio I G' / I G of the G' band to the G band as determined by Raman spectroscopy of the negative electrode active material particles is preferably 0≦I G' / I G ≦0.05. If 0≦I G' / I G ≦0.05, Li is inserted uniformly from the entire carbon surface during charging, resulting in better battery characteristics.
[0077] In the negative electrode active material of the present invention, the intensity ratio ISi / IG of the Si peak intensity and the G band in Raman spectroscopy of the negative electrode active material particles is preferably 0≦ISi / IG≦1.0. If 0≦ISi / IG≦1.0, the surface exposure of the silicon-based compound particles can be suppressed and gas generation in the aqueous slurry can be delayed, resulting in better battery characteristics.
[0078] [Method of manufacturing the negative electrode] Next, an example of a method for producing the negative electrode of the nonaqueous electrolyte secondary battery of the present invention will be described.
[0079] First, we will explain the manufacturing method of the negative electrode material contained in the negative electrode. x Silicon compounds (SiO x (x≦0.5≦x≦1.6) is prepared. Next, at least a portion of the silicon compound particle is coated with a carbon material. Next, Li is inserted into the silicon compound particle to modify the silicon compound particle. During this Li insertion, Li may also be removed. By this Li insertion, Li 2 SiO 3 and the Li content is set to 9.7% by mass or more and less than 13.2% by mass relative to the negative electrode active material particles. At the same time, Li compounds can be generated inside and on the surfaces of silicon compound particles. Then, when the negative electrode active material particles after modification are measured by X-ray diffraction using Cu-Kα rays, the intensity Ia of the peak at about 2θ=47.5° due to Si obtained by the X-ray diffraction and the intensity Ib of Li obtained by the X-ray diffraction are 2 SiO 3The peak intensity Ib of the peak at about 2θ=18.7° resulting from the above is selected to satisfy 1≦Ib / Ia≦18. A negative electrode material and a negative electrode can be produced by using the negative electrode active material particles containing such silicon compound particles and mixing them with a conductive assistant and a binder.
[0080] More specifically, the negative electrode active material is produced, for example, by the following procedure.
[0081] First, the raw material that generates silicon oxide gas is heated in the presence of an inert gas or under reduced pressure at a temperature range of 900°C to 1600°C to generate silicon oxide gas. In this case, the raw material is a mixture of metal silicon powder and silicon dioxide powder, and considering the surface oxygen of the metal silicon powder and the presence of trace oxygen in the reactor, the mixed molar ratio is preferably in the range of 0.8<metal silicon powder / silicon dioxide powder<1.3. The Si crystallites in the particles are controlled by changing the feeding range and vaporization temperature, and by heat treatment after generation. The generated gas is deposited on an adsorption plate. The temperature inside the reactor is lowered to below 100°C, and the deposit is taken out and crushed and powdered using a ball mill, jet mill, etc.
[0082] Next, a carbon coating is formed on the surface of the obtained silicon oxide powder material (silicon compound particles), which is effective in further improving the battery characteristics of the negative electrode active material.
[0083] Pyrolytic CVD is a preferred method for forming a carbon coating on the surface of a powder material. In pyrolytic CVD, silicon oxide powder is placed in a furnace, which is then filled with hydrocarbon gas to raise the temperature inside the furnace. There are no particular limitations on the decomposition temperature, but it is particularly preferred that it be 1200°C or lower. A temperature of 950°C or lower is even more preferred, as this makes it possible to suppress unintended disproportionation of silicon oxide. There are no particular limitations on the hydrocarbon gas, but it is preferred that it be C n H m Among the compositions, 2≧n is preferred because this leads to low production costs and good physical properties of the decomposition products.
[0084] Next, Li was inserted into the negative electrode active material particles containing the silicon active material particles prepared as described above,2 SiO 3 The insertion of Li is preferably carried out by an electrochemical method or a redox method.
[0085] In the electrochemical reforming, the structure of the apparatus is not particularly limited, but the in-bulk reforming can be performed, for example, by using an in-bulk reforming apparatus 20 shown in FIG. 2. The in-bulk reforming apparatus 20 has a bath 27 filled with an organic solvent 23, a positive electrode (lithium source, reforming source) 21 arranged in the bath 27 and connected to one side of a power supply 26, a powder storage container 25 arranged in the bath 27 and connected to the other side of the power supply 26, and a separator 24 provided between the positive electrode 21 and the powder storage container 25. The powder storage container 25 stores silicon oxide powder 22. The powder storage container stores a silicon compound (silicon oxide particles), and a voltage is applied from the power source to the powder storage container storing the silicon oxide particles and the positive electrode (lithium source). This allows lithium to be inserted into and removed from the silicon compound particles, so that the silicon oxide powder 22 can be reformed. The resulting silicon oxide can be heat-treated at 400 to 800°C to stabilize the Li compound.
[0086] As the organic solvent 23 in the bath 27, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, etc. can be used. In addition, as the electrolyte salt contained in the organic solvent 23, lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) etc. can be used.
[0087] The positive electrode 21 may be a Li foil or a Li-containing compound such as lithium carbonate, lithium oxide, lithium cobalt oxide, lithium iron olivine, lithium nickel oxide, or lithium vanadium phosphate.
[0088] After electrochemical Li-doping, the slurry may be washed with alkaline water containing lithium carbonate, lithium oxide, or lithium hydroxide dissolved therein, alcohol, weak acid, or pure water. By washing, the excess alkaline components can be eluted, improving the slurry stability.
[0089] In the modification by the oxidation-reduction method, for example, first, lithium can be inserted by immersing silicon active material particles in solution A in which lithium is dissolved in an ether solvent. This solution A may further contain a polycyclic aromatic compound or a linear polyphenylene compound. The Li compound can be stabilized by heat treating the obtained silicon oxide at 400 to 800 ° C. In addition, after lithium insertion, active lithium can be desorbed from the silicon active material particles by immersing the silicon active material particles in solution B containing a polycyclic aromatic compound or a linear polyphenylene compound or a derivative thereof. The solvent for this solution B can be, for example, an ether solvent, a ketone solvent, an ester solvent, an alcohol solvent, an amine solvent, or a mixture thereof. It may be washed with alkaline water, alcohol, weak acid, or pure water in which lithium carbonate, lithium oxide, or lithium hydroxide is dissolved. By washing, excess alkaline components can be eluted, and the slurry stability is improved.
[0090] As the ether solvent used in solution A, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, or a mixture thereof can be used. Among these, it is particularly preferable to use tetrahydrofuran, dioxane, 1,2-dimethoxyethane, or diethylene glycol dimethyl ether. These solvents are preferably dehydrated and deoxygenated.
[0091] The polycyclic aromatic compound contained in solution A may be one or more of naphthalene, anthracene, phenanthrene, naphthalene, pentacene, pyrene, triphenylene, coronene, chrysene, and derivatives thereof, and the linear polyphenylene compound may be one or more of biphenyl, terphenyl, and derivatives thereof.
[0092] The polycyclic aromatic compound contained in solution B may be one or more of naphthalene, anthracene, phenanthrene, naphthalene, pentacene, pyrene, triphenylene, coronene, chrysene, and derivatives thereof.
[0093] As the ether solvent for solution B, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, or a mixture of these solvents can be used.
[0094] As the ketone solvent, acetone, acetophenone, etc. can be used.
[0095] As the ester solvent, methyl formate, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, and the like can be used.
[0096] As the alcohol-based solvent, methanol, ethanol, propanol, isopropyl alcohol, and the like can be used.
[0097] As the amine solvent, methylamine, ethylamine, ethylenediamine, and the like can be used.
[0098] Li may also be inserted into the negative electrode active material particles by thermal doping. In this case, for example, the negative electrode active material particles are mixed with LiH powder or Li powder, and the mixture is heated under a non-oxidizing atmosphere to modify the material. For example, an Ar atmosphere can be used as the non-oxidizing atmosphere. More specifically, LiH powder or Li powder is first thoroughly mixed with silicon oxide powder under an Ar atmosphere, sealed, and homogenized by stirring the sealed container. Then, the mixture is heated in the range of 700°C to 750°C to modify the material. In this case, in order to remove Li from the silicon compound, the powder after heating may be thoroughly cooled and washed with alkaline water, alcohol, weak acid, or pure water in which lithium carbonate, lithium oxide, or lithium hydroxide is dissolved. By washing, excess alkaline components can be eluted, improving the slurry stability.
[0099] <Water-based negative electrode slurry composition> The negative electrode active material prepared as described above can be mixed with other materials such as a negative electrode binder and a conductive assistant as necessary, and then water can be added (an organic solvent or the like can also be added in addition to water) to obtain an aqueous negative electrode slurry composition.
[0100] Such an aqueous negative electrode slurry composition can suppress deterioration over time due to gas generation during storage, etc., and therefore has a high degree of freedom in the manufacturing process and is suitable for industrialization. In addition, by preparing an anode using the aqueous negative electrode slurry composition, a secondary battery having a high capacity and good initial charge / discharge characteristics can be obtained.
[0101] Next, the above-mentioned aqueous negative electrode slurry composition is applied to the surface of the negative electrode current collector and dried to form a negative electrode active material layer. At this time, hot pressing or the like may be performed as necessary. In this manner, the negative electrode can be produced.
[0102] <Lithium-ion secondary battery> Next, a laminate film type lithium ion secondary battery will be described as a specific example of the nonaqueous electrolyte secondary battery of the present invention.
[0103] [Configuration of laminated film type secondary battery] The laminate film type lithium ion secondary battery 30 shown in FIG. 3 is a battery in which a wound electrode body 31 is housed inside a sheet-like exterior member 35. This wound electrode body 31 has a separator between the positive electrode and the negative electrode and is wound. There are also cases where the electrode body is not wound, but a laminate having a separator between the positive electrode and the negative electrode is housed. In both electrode bodies, a positive electrode lead 32 is attached to the positive electrode, and a negative electrode lead 33 is attached to the negative electrode. The outermost periphery of the electrode body is protected by a protective tape.
[0104] The positive and negative electrode leads 32, 33 are led out in one direction, for example, from the inside to the outside of the exterior member 35. The positive electrode lead 32 is formed of a conductive material such as aluminum, and the negative electrode lead 33 is formed of a conductive material such as nickel or copper.
[0105] The exterior member 35 is, for example, a laminate film in which a fusion layer, a metal layer, and a surface protection layer are laminated in this order, and the outer peripheral edges of the fusion layers of the two films of this laminate film are fused together or pasted together with an adhesive so that the fusion layer faces the electrode body 31. The fusion part is, for example, a film such as polyethylene or polypropylene, and the metal part is aluminum foil, etc. The protection layer is, for example, nylon, etc.
[0106] An adhesive film 34 is inserted between the exterior member 35 and the positive and negative electrode leads to prevent outside air from entering. The material for this is, for example, polyethylene, polypropylene, or polyolefin resin.
[0107] The positive electrode has a positive electrode active material layer on either or both sides of a positive electrode current collector, similar to the negative electrode 10 in FIG.
[0108] The positive electrode current collector is made of a conductive material such as aluminum.
[0109] The positive electrode active material layer contains one or more positive electrode materials capable of absorbing and releasing lithium ions, and may contain other materials such as a positive electrode binder, a positive electrode conductive assistant, a dispersant, etc. In this case, details regarding the positive electrode binder and the positive electrode conductive assistant are the same as those of the negative electrode binder and the negative electrode conductive assistant already described, for example.
[0110] The positive electrode material is preferably a lithium-containing compound. Examples of the lithium-containing compound include a composite oxide made of lithium and a transition metal element, or a phosphate compound containing lithium and a transition metal element. Among these positive electrode materials, compounds containing at least one of nickel, iron, manganese, and cobalt are preferred. Examples of the chemical formula of these compounds include Li x M 1 O 2 Or Li y M 2 PO 4 In the formula, M 1 , M 2 represents at least one transition metal element. The values of x and y vary depending on the charge / discharge state of the battery, but are generally expressed as 0.05≦x≦1.10 and 0.05≦y≦1.10.
[0111] Examples of composite oxides containing lithium and transition metal elements include lithium cobalt composite oxide (Li x Chief of Staff 2 ), lithium nickel composite oxide (Li x NiO 2 Examples of the lithium nickel cobalt composite oxide include lithium nickel cobalt aluminum composite oxide (NCA) and lithium nickel cobalt manganese composite oxide (NCM).
[0112] Examples of phosphate compounds containing lithium and a transition metal element include lithium iron phosphate compounds (LiFePO 4 ) or lithium iron manganese phosphate (LiFe 1-u Mn u PO 4Examples include (0 < u < 1). When these cathode materials are used, high battery capacity can be obtained, and excellent cycle characteristics can also be obtained.
[0113] [Negative electrode] The negative electrode has the same configuration as the negative electrode 10 for a lithium-ion secondary battery shown in FIG. 1 above. For example, it has negative electrode active material layers on both sides of the current collector. It is preferable that the negative electrode charging capacity is larger than the electrical capacity (charging capacity as a battery) obtained from the cathode active material agent. This can suppress the precipitation of lithium metal on the negative electrode.
[0114] The positive electrode active material layer is provided on a part of both sides of the positive electrode current collector. Similarly, the negative electrode active material layer is also provided on a part of both sides of the negative electrode current collector. In this case, for example, the negative electrode active material layer provided on the negative electrode current collector has a region where there is no opposing positive electrode active material layer. This is for stable battery design.
[0115] In the region where the above negative electrode active material layer and positive electrode active material layer do not face each other, it is hardly affected by charge and discharge. Therefore, the state of the negative electrode active material layer is maintained as it is immediately after formation, and thus the composition of the negative electrode active material can be accurately investigated with good reproducibility without depending on the presence or absence of charge and discharge.
[0116] [Separator] The separator separates the positive electrode and the negative electrode, prevents current short-circuiting due to contact between the two electrodes, and allows lithium ions to pass through. This separator is formed, for example, by a porous membrane made of a synthetic resin or a ceramic, and may have a laminated structure in which two or more porous membranes are laminated. Examples of synthetic resins include polytetrafluoroethylene, polypropylene, polyethylene, and the like.
[0117] [Electrolyte solution] At least a part of the active material layer or the separator is impregnated with a liquid electrolyte (electrolyte solution). This electrolyte solution has an electrolyte salt dissolved in a solvent and may contain other materials such as additives.
[0118] The solvent may be, for example, a non-aqueous solvent. Examples of the non-aqueous solvent include ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, 1,2-dimethoxyethane, and tetrahydrofuran. Among these, it is desirable to use at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. This is because better characteristics can be obtained. In this case, more advantageous characteristics can be obtained by combining a high-viscosity solvent such as ethylene carbonate or propylene carbonate with a low-viscosity solvent such as dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. This is because the dissociation property and ion mobility of the electrolyte salt are improved.
[0119] It is preferable that the solvent additive contains an unsaturated carbon-bonded cyclic carbonate. This is because a stable coating is formed on the negative electrode surface during charging and discharging, and the decomposition reaction of the electrolyte can be suppressed. Examples of the unsaturated carbon-bonded cyclic carbonate include vinylene carbonate and vinylethylene carbonate.
[0120] It is also preferable that the solvent additive contains sultone (cyclic sulfonic acid ester), because this improves the chemical stability of the battery. Examples of sultones include propane sultone and propene sultone.
[0121] Furthermore, it is preferable that the solvent contains an acid anhydride, because this improves the chemical stability of the electrolyte. As the acid anhydride, for example, propane disulfonic acid anhydride can be mentioned.
[0122] The electrolyte salt may include at least one of light metal salts such as a lithium salt. Examples of the lithium salt include lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) etc.
[0123] The content of the electrolyte salt is preferably 0.5 mol / kg or more and 2.5 mol / kg or less relative to the solvent, because this provides high ionic conductivity.
[0124] [Manufacturing method of laminate film type secondary battery] First, a positive electrode is prepared using the above-mentioned positive electrode material. First, a positive electrode active material is mixed with a positive electrode binder, a positive electrode conductive assistant, etc., if necessary, to prepare a positive electrode mixture, which is then dispersed in an organic solvent to prepare a positive electrode mixture slurry. Next, the mixture slurry is applied to a positive electrode current collector using a coating device such as a knife roll or a die coater having a die head, and the mixture is dried with hot air to obtain a positive electrode active material layer. Finally, the positive electrode active material layer is compression molded using a roll press machine or the like. At this time, heating may be performed, and compression may be repeated multiple times.
[0125] Next, using the same procedure as in the production of the lithium ion secondary battery negative electrode 10 described above, a negative electrode active material layer is formed on the negative electrode current collector to produce the negative electrode.
[0126] When preparing the positive and negative electrodes, active material layers are formed on both sides of the positive and negative current collectors, respectively. At this time, the lengths of the active material applied on both sides of each electrode may be offset (see FIG. 1).
[0127] Next, the electrolyte is adjusted. Next, the positive electrode lead 32 is attached to the positive electrode current collector by ultrasonic welding or the like, and the negative electrode lead 33 is attached to the negative electrode current collector. Next, the positive electrode and the negative electrode are laminated or wound with a separator interposed therebetween to prepare a wound electrode body 31, and a protective tape is attached to the outermost periphery. Next, the wound body is molded to have a flat shape. Next, the wound electrode body is sandwiched between folded film-like exterior members 35, and then the insulating parts of the exterior members are bonded to each other by a heat fusion method, and the wound electrode body is enclosed in a state in which only one direction is open. Next, an adhesive film is inserted between the positive electrode lead and the negative electrode lead and the exterior member. Next, a predetermined amount of the above-prepared electrolyte is poured from the open portion, and vacuum impregnation is performed. After impregnation, the open portion is bonded by a vacuum heat fusion method. In this manner, a laminate film type secondary battery 30 can be manufactured.
[0128] In the nonaqueous electrolyte secondary battery of the present invention, such as the laminate film type secondary battery 30 prepared above, the negative electrode utilization rate during charging and discharging is preferably 93% or more and 99% or less. If the negative electrode utilization rate is in the range of 93% or more, the initial charge efficiency does not decrease and the battery capacity can be greatly improved. In addition, if the negative electrode utilization rate is in the range of 99% or less, Li does not precipitate and safety can be ensured. EXAMPLES
[0129] The present invention will be described in more detail below by showing examples and comparative examples of the present invention, but the present invention is not limited to these examples.
[0130] (Example 1-1) The laminate film type secondary battery 30 shown in FIG. 3 was fabricated by the following procedure.
[0131] First, the positive electrode was prepared. The positive electrode active material was lithium nickel cobalt aluminum composite oxide (LiNi 0.7 Co 0.25 Al 0.05 A positive electrode mixture was prepared by mixing 95 parts by mass of ethylenediaminetetraacetate (FeO), 2.5 parts by mass of a positive electrode conductive assistant (acetylene black), and 2.5 parts by mass of a positive electrode binder (polyvinylidene fluoride, PVDF). The positive electrode mixture was then dispersed in an organic solvent (N-methyl-2-pyrrolidone, NMP) to form a paste-like slurry. The slurry was then applied to both sides of the positive electrode current collector using a coating device with a die head, and dried using a hot air drying device. At this time, a positive electrode current collector with a thickness of 15 μm was used. Finally, compression molding was performed using a roll press.
[0132] Next, the negative electrode was prepared. First, the silicon-based active material was prepared as follows. A raw material (vaporized starting material) made by mixing metal silicon and silicon dioxide was placed in a reactor, and the material was vaporized in a vacuum atmosphere of 10 Pa and deposited on an adsorption plate. After sufficient cooling, the deposit was taken out and pulverized with a ball mill. After adjusting the particle size, a carbon film was coated by performing thermal CVD. Next, lithium was inserted into the silicon compound particles coated with the carbon film by an oxidation-reduction method to modify the silicon compound. First, the negative electrode active material particles were immersed in a solution (solution A) in which lithium pieces and naphthalene, an aromatic compound, were dissolved in tetrahydrofuran (hereinafter referred to as THF). This solution A, a THF solvent, was dissolved in a concentration of 0.2 mol / L, and then 12% by mass of lithium pieces were added to the mixture of THF and naphthalene to prepare the solution. The temperature of the solution when the negative electrode active material particles were immersed was 20° C., and the immersion time was 20 hours. The negative electrode active material particles were then filtered out. By the above-mentioned treatment, lithium was inserted into the negative electrode active material particles.
[0133] The obtained silicon compound particles were heat-treated in an argon atmosphere at 650°C or less for 24 hours to stabilize the Li compound.
[0134] In this way, the negative electrode active material particles (silicon-based active material particles) were modified. The above treatment produced negative electrode active material particles. The Li content of the negative electrode active material particles was 10.0 mass%, the carbon coverage was 3 mass%, and the median diameter (volume basis, D50) of the negative electrode active material particles was 8.9 μm.
[0135] XRD measurement of the obtained negative electrode active material particles, 29 Si-NMR measurement, Raman spectroscopy analysis, and particle size distribution measurement were performed.
[0136] The silicon-based active material prepared as above was mixed with a carbon-based active material in a mass ratio of 2:8 to prepare a negative electrode active material. Here, as the carbon-based active material, a mixture of natural graphite and artificial graphite coated with a pitch layer in a mass ratio of 5:5 was used. The median diameter of the carbon-based active material was 20 μm.
[0137] Next, the prepared negative electrode active material, conductive assistant 1 (carbon nanotube, CNT), conductive assistant 2 (carbon fine particles with a median diameter of about 50 nm), styrene butadiene rubber (styrene butadiene copolymer, hereinafter referred to as SBR), and carboxymethyl cellulose (hereinafter referred to as CMC) were mixed in a dry mass ratio of 92.5:1:1:2.5:3, and then diluted with pure water to form a negative electrode mixture slurry. The above SBR and CMC are negative electrode binders (negative electrode binders). Here, in order to measure the stability of the negative electrode mixture slurry, 30 g of a part of the prepared negative electrode mixture slurry was taken out separately from that for the preparation of the secondary battery, and stored at 20 ° C., and the gas generation state was confirmed after the preparation of the negative electrode mixture slurry. This gas generation state was evaluated by the time from the preparation of the slurry until gas generation. It can be said that the longer this time, the more stable the slurry is.
[0138] In addition, electrolytic copper foil (thickness 15 μm) was used as the negative electrode current collector. Finally, the negative electrode mixture slurry was applied to the negative electrode current collector and dried at 100° C. for 1 hour in a vacuum atmosphere. After drying, the deposition amount of the negative electrode active material layer per unit area on one side of the negative electrode (also called the area density) was 5 mg / cm. 2 It was.
[0139] Next, fluoroethylene carbonate (FEC), ethylene carbonate (EC), and diethyl carbonate (DEC) were mixed as a solvent, and then an electrolyte salt (lithium hexafluorophosphate: LiPF 6 ) was dissolved to prepare an electrolyte solution. In this case, the solvent composition was FEC:EC:DEC = 1:2:7 in volume ratio, and the content of the electrolyte salt was 1.0 mol / kg relative to the solvent. Furthermore, 1.5 mass% of vinylene carbonate (VC) was added to the obtained electrolyte solution.
[0140] Next, a secondary battery was assembled as follows. First, an aluminum lead was ultrasonically welded to one end of the positive electrode current collector, and a nickel lead was welded to the negative electrode current collector. Next, the positive electrode, separator, negative electrode, and separator were laminated in this order and wound in the longitudinal direction to obtain a wound electrode body. The end of the winding was fixed with a PET protective tape. The separator used was a laminated film of 12 μm in which a film mainly composed of porous polypropylene was sandwiched between a film mainly composed of porous polyethylene. Next, the electrode body was sandwiched between the exterior members, and then the outer peripheral edges except for one side were heat-sealed to store the electrode body inside. The exterior member used was an aluminum laminate film in which a nylon film, aluminum foil, and a polypropylene film were laminated. Next, the adjusted electrolyte was injected from the opening, impregnated under a vacuum atmosphere, and then heat-sealed and sealed.
[0141] The cycle characteristics and initial charge / discharge characteristics of the secondary battery thus fabricated were evaluated.
[0142] The cycle characteristics were investigated as follows. First, in order to stabilize the battery, two cycles of charging and discharging were performed at 0.2C in an atmosphere of 25°C, and the discharge capacity of the second cycle was measured. Next, charging and discharging were performed until the total number of cycles reached 299, and the discharge capacity was measured each time. Finally, the discharge capacity of the 300th cycle obtained by charging and discharging at 0.2C was divided by the discharge capacity of the second cycle to calculate the capacity retention rate (hereinafter also simply referred to as the retention rate). In the normal cycles, that is, from the third cycle to the 299th cycle, charging and discharging were performed at 0.7C for charging and 0.5C for discharging.
[0143] When investigating the initial charge / discharge characteristics, the initial efficiency (hereinafter sometimes referred to as initial efficiency) was calculated. The initial efficiency was calculated from the formula: initial efficiency (%) = (initial discharge capacity / initial charge capacity) x 100. The atmospheric temperature was the same as when investigating the cycle characteristics. In addition, this initial efficiency was calculated based on the discharge capacity up to 1.2V.
[0144] (Comparative Examples 1-1 and 1-2) Secondary batteries were produced and evaluated under the same conditions as in Example 1-1, except that the peak intensity ratio Ib / Ia of X-ray diffraction in silicon-based negative electrode active material particles was changed as shown in Table 1. The peak intensity ratio Ib / Ia was adjusted by the Li content and heat treatment conditions (temperature, time).
[0145] The evaluation results of Example 1-1 and Comparative Examples 1-1 and 1-2 are shown in Table 1.
[0146] [Table 1]
[0147] As shown in Table 1, in silicon compounds represented by SiOx, when the intensity ratio Ib / Ia exceeds 18, Li 2 SiO 3 The peak intensity of Li is too strong, resulting in deterioration of the battery characteristics. 2 SiO 3 The peak intensity of Ib / Ia is strong, and the initial efficiency is poor. On the other hand, in Comparative Example 1-2, the Si peak is strong, and gas generation in the slurry is intense, resulting in deterioration of the battery characteristics. On the other hand, when the intensity ratio Ib / Ia is 18 or less, there is no problem with the slurry stability, and good battery characteristics (high initial efficiency and cycle retention rate) are obtained.
[0148] (Examples 2-1 to 2-5, Comparative Examples 2-1 and 2-2) A secondary battery was produced in the same manner as in Example 1-1, except that the Li content of the silicon compound particles and the peak intensity ratio Ib / Ia of X-ray diffraction were adjusted. The Li content was adjusted by adjusting the Li doping amount.
[0149] The Li content was adjusted as shown in Table 2. As a result, when the Li content was 13.2 mass% or more, the slurry stability was deteriorated and battery evaluation could not be performed. For example, as shown in Comparative Example 2-2, when the Li content was 13.2 mass% or more, the slurry stability was deteriorated, making it difficult to prepare an electrode and making it impossible to evaluate a battery. On the other hand, when the Li content was low (9.4 mass%) as shown in Comparative Example 2-1, no improvement in battery characteristics was observed.
[0150] [Table 2]
[0151] (Examples 3-1 to 3-10) The Li compound (crystalline Li 2 CO 3 and LiOH H 2 Except for adjusting the amount of LiO produced, secondary batteries were produced under the same conditions as in Example 1-1 and were evaluated. 2 CO 3 ,LiOH·H 2 It is possible to adjust O by adjusting the time of exposure to the atmosphere. Table 3 shows the evaluation results of Example 1-1 and Example 3-1 to Example 3-10.
[0152] [Table 3]
[0153] As shown in Table 3, when the Ic / Ia intensity ratio of each peak in the X-ray diffraction spectrum is 10 or less, the initial efficiency is higher and the number of days for gas generation is also good. As a result, the battery characteristics are improved. On the other hand, when Id / Ia is 20 or less, the initial efficiency is lowered and the number of days for gas generation is improved.
[0154] (Examples 4-1 to 4-7) Next, secondary batteries were produced under the same conditions as in Example 1-1, except that the crystallite size of the Si (220) plane in the negative electrode active material particles was adjusted, and each evaluation was performed. This crystallite size can be adjusted by the heat load of the silicon oxide. The evaluation results of Example 1-1 and Example 4-1 to Example 4-7 are shown in Table 4.
[0155] [Table 4]
[0156] As shown in Table 4, when the crystallite size was 5 nm or less, gas generation was suppressed and better battery characteristics were obtained.
[0157] (Examples 5-1 to 5-5, Comparative Example 5-1) Next, the Li 2 SiO 3 A secondary battery was produced under the same conditions as in Example 1-1, except that the half-width of the peak was adjusted, and each evaluation was performed. The half-width of the peak was adjusted by the heat treatment conditions (temperature, time). The evaluation results of Example 1-1, Example 5-1 to Example 5-5, and Comparative Example 5-1 are shown in Table 5.
[0158] [Table 5]
[0159] As shown in Table 5, Li 2 SiO 3 When the half-width of the peak exceeds 3°, the Li content tends to be high. In other words, when the Li content is too high, 2 SiO 3 In this case, gas generation from the slurry becomes significant, which leads to a deterioration in the battery characteristics. 2 SiO 3 The half width of the angle is preferably 0.5° or more and 3° or less.
[0160] (Examples 6-1 to 6-10) Next, secondary batteries were produced under the same conditions as in Example 1-1, except that the peak intensity ratios Ie / Ig and If / Ig in the negative electrode active material particles were adjusted, and each evaluation was performed. The peak intensity ratio can be adjusted by the heat treatment conditions of the Li-containing silicon oxide. The evaluation results of Examples 6-1 to 6-10 are shown in Table 6.
[0161] [Table 6]
[0162] As shown in Table 6, when Ie / Ig was 0.23 or less and If / Ig was 1.1 or less, the doped Li was sufficiently stabilized, so that gas generation during slurry preparation was suppressed and good battery characteristics were observed.
[0163] (Examples 7-1 to 7-5) Next, secondary batteries were produced under the same conditions as in Example 1-1, except that the amount of carbon coating on the negative electrode active material particles was adjusted, and each evaluation was performed. The amount of carbon coating can be adjusted by the thermal CVD time. The evaluation results of Example 1-1 and Examples 7-1 to 7-5 are shown in Table 7.
[0164] [Table 7]
[0165] As shown in Table 7, when the carbon coating amount is 0.3 mass% or more, there is a sufficient hydrophobic film on the surface, which suppresses the elution of doped Li and suppresses gas generation in the slurry. In addition, when the carbon coating amount is 0.3 mass% or more, there is a sufficient conductive film on the surface, which improves the initial efficiency and capacity retention rate at 300 cycles.
[0166] (Example 8-1 to Example 8-7) Next, secondary batteries were produced under the same conditions as in Example 1-1, except that the intensity ratios of ID / IG, IG' / IG, and ISi / IG were adjusted by Raman spectroscopy in the negative electrode active material particles, and each evaluation was performed. These peak intensity ratios can be adjusted by the conditions (temperature, pressure, gas flow rate) during thermal CVD. The evaluation results of Example 1-1 and Example 8-1 to Example 8-7 are shown in Table 8.
[0167] [Table 8]
[0168] As shown in Table 8, the ID / IG intensity ratio is preferably in the range of 0.4 to 1.1. Within this range, the sp3 component is not too much, so the conductivity of the carbon film is good and excellent battery characteristics are obtained. In addition, IG' / IG is preferably 0.05 or less. By making IG' / IG 0.05 or less, side reactions during charging are suppressed, resulting in good battery characteristics. In addition, ISi / IG is preferably 1.0 or less. If ISi / IG exceeds 1.1, there will be a large amount of exposed surface that is not covered with the carbon coating, which will cause gas generation in the slurry, resulting in a slight decrease in battery characteristics.
[0169] (Examples 9-1 to 9-7) Next, secondary batteries were produced under the same conditions as in Example 1-1 except that D10 (particle size of 10% on a volume cumulative basis) and D50 (median diameter) of the silicon compound particles were changed, and each evaluation was performed. The evaluation results of Example 1-1 and Examples 9-1 to 9-7 are shown in Table 9. [Table 9]
[0170] When the median diameter of the silicon compound particles is 0.5 μm or more, particularly 3 μm or more, the initial efficiency and the maintenance rate are improved. This is thought to be because the surface area of the silicon compound particles is not too large, which suppresses side reactions. On the other hand, when the median diameter is 20 μm or less, the particles are less likely to break during charging, and the SEI (solid electrolyte interface) due to the newly formed surface is less likely to be generated during charging and discharging, so that the loss of reversible Li can be suppressed. In addition, when the median diameter of the silicon compound particles is 20 μm or less, the amount of expansion of the silicon compound particles during charging does not become too large, so that physical and electrical destruction of the negative electrode active material layer due to expansion can be prevented. In addition, it is preferable that D10 is 2 μm or more and 16 μm or less.
[0171] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]
[0172] 10...Negative electrode, 11...Negative electrode current collector, 12...Negative electrode active material layer, 20... Bulk reformer, 21... Positive electrode (lithium source, reformer source), 22...Silicon compound particles (silicon compound particles having a carbon coating), 23...organic solvent, 24...separator, 25...powder storage container, 26...power supply, 27...bathtub, 30...Lithium secondary battery (laminate film type), 31...electrode body, 32...Positive electrode lead (positive electrode aluminum lead), 33...Negative electrode lead (negative electrode nickel lead), 34...adhesive film, 35...exterior part.
Claims
1. The negative electrode active material particles are made of a silicon compound (SiO x : 0.5≦x≦1.6) particles, the negative electrode active material particles are at least partially coated with a carbon material, the negative electrode active material particles contain Li, and the Li content is 9.7% by mass or more and less than 13.2% by mass with respect to the negative electrode active material particles; At least a part of the Li is Li 2 SiO 3 exists as When the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα radiation, the intensity of the peak at 2θ=47.5° due to Si obtained by the X-ray diffraction is Ia, and the intensity of the peak at 2θ=47.5° due to Li obtained by the X-ray diffraction is Ib. 2 SiO 3 a peak intensity Ib of a peak at about 2θ=18.7° resulting from the above satisfies 1≦Ib / Ia≦18.
2. The negative electrode active material particles have a crystalline Li 2 CO 3 and LiOH.H 2 2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, which does not contain O.
3. The negative electrode active material particles have a crystalline Li 2 CO 3 and LiOH.H 2 At least one of O is included, When the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα rays, the Li obtained by the X-ray diffraction 2 CO 3 The peak intensity Ic at about 2θ=21° due to satisfies 0≦Ic / Ia≦10, and the LiOH.H obtained by the X-ray diffraction 2 2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein a peak intensity Id attributable to O at about 2θ=32° satisfies 0≦Id / Ia≦20.
4. 4. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein, when the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα radiation, the crystallite size resulting from the Si(220) crystal plane obtained by the X-ray diffraction is 5 nm or less.
5. When the negative electrode active material particles are measured by X-ray diffraction using Cu-Kα rays, the Li obtained by the X-ray diffraction 2 SiO 3 5. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein a half-width of a peak attributable to the above is in the vicinity of 2θ=18.7° is 0.5° or more and 3.0° or less.
6. The negative electrode active material particles 29 6. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the negative electrode active material has at least one peak in at least one of the following chemical shift values obtained from a Si-MAS-NMR spectrum: a region of not less than −80 ppm and not more than −70 ppm, a region of not less than −70 ppm and not more than −60 ppm, and a region of not less than −60 ppm and not more than −30 ppm.
7. The negative electrode active material particles 29 7. The negative electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein Ie is a peak intensity of a peak obtained in a chemical shift value region of -60 ppm or more and less than -30 ppm, If is a peak intensity of a peak obtained in a chemical shift value region of -70 ppm or more and less than -60 ppm, and Ig is a peak intensity of a peak obtained in a chemical shift value region of -80 ppm or more and less than -70 ppm, as obtained from a Si-MAS-NMR spectrum, and 0≦Ie / Ig≦0.23 and 0≦If / Ig≦1.1 are satisfied.
8. 8. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein an amount of carbon coating on the negative electrode active material particles is 0.3 mass % or more and 10 mass % or less with respect to a total amount of the silicon compound particles and the carbon coating layer.
9. 9. The negative electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein an intensity ratio ID / IG of a D band to a G band by Raman spectroscopy of the negative electrode active material satisfies 0.4≦ID / IG≦1.
1.
10. 10. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein an intensity ratio I G' / I G of a G' band to a G band by Raman spectroscopic analysis of the negative electrode active material is 0≦I G' / I G ≦0.
05.
11. 11. The negative electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein a ratio I / I of a Si peak intensity to a G band intensity by Raman spectroscopy of the negative electrode active material satisfies 0≦I / I≦1.
0.
12. 12. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the silicon compound particles have a median diameter of 0.5 μm or more and 20 μm or less.
13. A non-aqueous electrolyte secondary battery comprising the negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 .
14. A method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery, comprising the steps of: Silicon compounds (SiO x : 0.5≦x≦1.6), A step of coating at least a portion of the silicon compound particles with a carbon material; Li is inserted into the silicon compound particles to form Li 2 SiO 3 and adjusting the Li content to 9.7% by mass or more and less than 13.2% by mass with respect to the negative electrode active material particles. Including, When the negative electrode active material particles thus produced are measured by X-ray diffraction using Cu-Kα radiation, the intensity of the peak at about 2θ=47.5° due to Si obtained by the X-ray diffraction is Ia, and the intensity of the peak at about 2θ=47.5° due to Li obtained by the X-ray diffraction is Ib. 2 SiO 3 a peak intensity Ib of a peak at about 2θ=18.7° resulting from the above satisfying 1≦Ib / Ia≦18.
Citation Information
Patent Citations
Negative electrode material for nonaqueous secondary battery and its manufacturing method, and lithium ion secondary battery
JP2011222153A
Negative electrode material for power storage device, electrode for power storage device, power storage device and method for manufacturing them
JP2014103019A
Powder for negative electrode of lithium ion secondary battery, and method of manufacturing the same
JP2015153520A
Negative electrode active material for nonaqueous electrolyte secondary battery and method for manufacturing the same
JP2020113465A
Negative electrode active material for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and manufacturing method of negative electrode material for nonaqueous electrolyte secondary battery
JP2020113495A